2012
DOI: 10.4103/0970-9185.92444
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of hyperbaric oxygen therapy in the management of chronic nonhealing ulcer and role of periwound transcutaneous oximetry as a predictor of wound healing response: A randomized prospective controlled trial

Abstract: Background:Hyperbaric oxygen therapy (HBOT) is a treatment option for chronic nonhealing wounds. Transcutaneous oximetry (TCOM) is used for wound assessment. We undertook a randomized prospective controlled trial to evaluate the role of HBOT in healing of chronic nonhealing wounds and to determine whether TCOM predicts healing.Materials and Methods:This study was conducted in 30 consenting patients with nonhealing ulcer. The patients were randomized into group HT (receiving HBOT in addition to conventional tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…Clinically, a positive correlation has been reported between tissue oxygenation and various markers of wound healing. These results support the efficacy of HBO 2 [19]. …”
Section: Discussionsupporting
confidence: 77%
“…Clinically, a positive correlation has been reported between tissue oxygenation and various markers of wound healing. These results support the efficacy of HBO 2 [19]. …”
Section: Discussionsupporting
confidence: 77%
“…HBOT has been recommended as a treatment for delayed radiation injury 94. In a randomized trial, a positive correlation was reported between tissue oxygenation and various markers of wound healing 95…”
Section: Therapy Of Risrsmentioning
confidence: 99%
“…Hyperbaric oxygen therapy (HBOT) is a safe, effective, and noninvasive treatment that has been applied to treat various conditions [6]. During HBOT, the patient is placed in a hyperbaric chamber, which pressurized to 1.4 atmospheres absolute (ATA) or higher and is supplemented with pure oxygen [7].…”
Section: Introductionmentioning
confidence: 99%